Fasciola hepatica occurrence in capybaras (Hydrochaeris hydrochaeris) and bovines (Bos taurus) in Timbó, SC, Brazil (Revista de Ciências Agroveterinárias, 2009)
The aim of this study was to evaluate the occurrence of Fasciola hepatica in the population from bovines (Bos taurus) and capybaras (Hydrochaeris hydrochaeris), during the period of August 2005 to July 2007. Samples of feces were collected directly from the rectum of 160 bovines, youngs and adults, born and raised in Timbó-SC, Brazil. A total number of 134 capybaras feces samples was collected at the environment with aspect of recent elimination. The samples were collected in 19 rural properties and at the city's Sportive Center, located nearby rivers. The samples were placed individually, identified and transported to the Laboratory of Parasitology and Parasitic Diseases of CAV/UDESC. The material was examined according to the "Quatro Tamises" technique. The bovine results demonstrated a F. hepatica's occurrence of 18.12% (29/160) with positive animals in 47.36% of the properties (9/19). Regarding the capybaras, 8.96% (12/134) of the samples were positive for F. hepatica eggs with positive animals in 25.0% (5/20) of the properties, including the Sportive Center. The results emphasized the influence of these animals as definitive hosts in the biological cycle of F. hepatica.
Keywords: hepatica; bovines; capybaras.